Petrography of Metamorphic Rocks from the Miller Range, Antarctica - Gunner, John D. (Research Foundation and the Institute of Polar Studies, The Ohio State University, 1969)
On cover: "RF 2494" Rock samples collected from the metamorphic rocks of the Nimrod Group in the Miller Range, Antarctica, comprise six lithological groups: mica schists, metaquartzites, banded gneisses, augen gneisses, marbles and amphibolites. Mineral parageneses indicate that these rocks have been regionally metamorphosed to the lower almandine-amphibolite facies of the Barrovian facies series. Chemical analyses calculated from petrographic modes of 13 representative thin sections indicate that the amphibolites were derived from basaltic rocks, but that the principal sources for the remaining five lithologies were sedimentary. National Science Foundation Grant GA-1159 Squadron VX-6, U.S. Naval Support Force, Antarctica